Pendidikan Kesehatan Dan Implementasi Manajemen Pencegahan Stroke Dengan Pergerakan Senam Anti Stroke - Kada, Maria Kurnyata Rante; Rusnita, Rusnita; Nursiah, Andi; Sima, Yenny; Mulia, Madepan; Noviar, Rizki Andita; Hoda, Ferdinandus Suban (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Stroke is a condition in which rapidly developing clinical signs are found in the form of focal and global neurological deficits, which can worsen and last for 24 hours or more and/or can cause death, without any other clear cause other than vascular. Lifestyle and socio-economic are suspected as one of the biggest factors causing stroke. The purpose of this community service activity is to improve community knowledge and skills about stroke prevention management. Activity method with. The results of the Community Service showed that participants were very enthusiastic during the Community Service activity and in addition, participants were also able to practice anti-stroke gymnastics movements correctly from start to finish. The conclusion is that this activity provides something positive for the community related to knowledge about how to prevent stroke with the Community Service Team hoping that anti-stroke gymnastics can be continued by the community at any time and anywhere.